2021
DOI: 10.1002/brb3.2376
|View full text |Cite
|
Sign up to set email alerts
|

Protective mechanism of FoxO1 against early brain injury after subarachnoid hemorrhage by regulating autophagy

Abstract: Introduction:Early brain injury (EBI) plays a key role in the devastating outcomes after subarachnoid hemorrhage (SAH). Autophagy and apoptosis may share a common molecular inducer that regulates the process of cell death. FoxO1, as a key regulator of neuronal autophagy which is involved in apoptosis, has not been reported in SAH rats.This work was to investigate the protective and anti-inflammatory effects of FoxO1 on EBI after SAH by regulating autophagy. Methods:In this study, we constructed the SAH model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 63 publications
(72 reference statements)
1
1
0
Order By: Relevance
“…Emerging evidence has revealed that modulating autophagy protected against SAH-induced brain injury [ 117 ]. Our recent study found that Acetyl CoA synthase 2 improved neurological deficits, brain edema, and neuronal death, which are shown to be responsible for poor outcomes after a SAH by enhancing autophagy [ 63 ], consistent with the results of Hao et al [ 118 ]. The activation of autophagy may be a promising strategy in the treatment of SAHs.…”
Section: The Therapeutic Role Of Sirt1 In Sahssupporting
confidence: 87%
“…Emerging evidence has revealed that modulating autophagy protected against SAH-induced brain injury [ 117 ]. Our recent study found that Acetyl CoA synthase 2 improved neurological deficits, brain edema, and neuronal death, which are shown to be responsible for poor outcomes after a SAH by enhancing autophagy [ 63 ], consistent with the results of Hao et al [ 118 ]. The activation of autophagy may be a promising strategy in the treatment of SAHs.…”
Section: The Therapeutic Role Of Sirt1 In Sahssupporting
confidence: 87%
“…Forkhead box protein O1 (FOXO1), a well-studied member of FOX family, acts as a transcription factor to modulate downstream targets involved in cell apoptosis, autophagy, cell cycle arrest, oxidative stress and immune regulation [ 17 ]. FOXO1 improves SAH-induced neurological function, brain edema, BBB leakage and inflammation by promoting autophagy in rat [ 18 ]. Intriguingly, low-dose LPS protects against ischemia/reperfusion (I/R)-induced neuronal apoptosis by increasing FOXO1 and phosphorylated FOXO1 (p-FOXO1) [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of simple anti infection interventions is significant. Early excessive inflammatory response and late immunosuppressive state are the pathological and physiological characteristics of sepsis, and immunotherapy for sepsis has become a current research hotspot [2]. A certain amount of researches [3][4][5] has shown that reducing the activation of the NLRP3/Caspase-1 pathway can significantly improve sepsis induced neuroinflammation and alleviate brain damage in sepsis.…”
mentioning
confidence: 99%